Fetal Exposure to Anti-Hypersensitive Drug, Zestoretic Delays Estrus Cycle and Suppresses Female Reproductive Potential in Rats at Their Adulthood - Ponneri Naveen; Sri Bhashyam Sainath; Arifullah Mohammed; Ramesh Koduru; Saeed Alshahrani; Ramachandra Reddy Pamuru; Ghazala Muteeb (Journal of Infertility and Reproductive Biology, 2025)
The current investigation is designed to explore the possible role of fetal exposure to the anti-hypersensitive drug zestoretic, a version of lisinopril (angiotensin-converting enzyme inhibitor) and hydrochlorothiazide (a diuretic drug) on female fertility efficacy in rats at their adulthood.The pregnant rats were oral gavaged withzestoretic 25, 50 and 100 mg/kg body weight on 7, 9, 11 and 13 days of gestation. The F1 female rats were tested with estrus cycle length and reproductive efficacy.Zestoreticfetal exposure induced significant change (P<0.001) in prolonged estrus cycles, reduced body weight, increased implantation loss and resorptions, conception time, mating index, and fertility index in female F1 rats, indicating potential harm to embryonic development and reduced fertility later in life.Though zestoretic reduces high blood pressure, its prenatal exposure harms F1 female reproductive health, causing prolonged estrus cycles, reduced fertility with increased conception time, resorptions and implantation loss. Although rat study results can’t directly apply to humans, caution and strict dosage adherence are advised when using anti-hypersensitive drugs during pregnancy.